2015
DOI: 10.1186/s13063-015-0720-3
|View full text |Cite
|
Sign up to set email alerts
|

Successful knowledge translation intervention in long-term care: final results from the vitamin D and osteoporosis study (ViDOS) pilot cluster randomized controlled trial

Abstract: BackgroundFew studies have systematically examined whether knowledge translation (KT) strategies can be successfully implemented within the long-term care (LTC) setting. In this study, we examined the effectiveness of a multifaceted, interdisciplinary KT intervention for improving the prescribing of vitamin D, calcium and osteoporosis medications over 12-months.MethodsWe conducted a pilot, cluster randomized controlled trial in 40 LTC homes (21 control; 19 intervention) in Ontario, Canada. LTC homes were eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(88 citation statements)
references
References 51 publications
4
83
1
Order By: Relevance
“…A meta-analysis by Cameron et al 35 reported that multifactorial interventions reduce falls and risk of falling in hospitals and may do so in nursing care facilities. They also reported that vitamin D supplementation significantly reduced the rate of falls (Relative attributable risk [RaR], 0.63; 95% confidence interval, 0.46 to 0.86; five trials, 4603 participants), thus confirming a recent report by Kennedy et al 30 supporting the correction of vitamin D deficiency as an effective intervention to prevent falls in this setting.…”
Section: Nonpharmacologicalsupporting
confidence: 64%
See 1 more Smart Citation
“…A meta-analysis by Cameron et al 35 reported that multifactorial interventions reduce falls and risk of falling in hospitals and may do so in nursing care facilities. They also reported that vitamin D supplementation significantly reduced the rate of falls (Relative attributable risk [RaR], 0.63; 95% confidence interval, 0.46 to 0.86; five trials, 4603 participants), thus confirming a recent report by Kennedy et al 30 supporting the correction of vitamin D deficiency as an effective intervention to prevent falls in this setting.…”
Section: Nonpharmacologicalsupporting
confidence: 64%
“…30 It is expected that the use of a similar structured and multidisciplinary approach, which includes pharmacological as well as nonpharmacological interventions, could be very useful in the Australian context where access to prescriptions for osteoporosis is highly regulated and based on evidence of cost effectiveness.…”
Section: Fracture Preventionmentioning
confidence: 99%
“…Approximately half of the studies evaluated quality improvement strategies for patient populations composed entirely of individuals with recent or prior fracture. Most studies reported outcomes of osteoporosis treatment and/or screening (BMD/DXA testing); only four reported fracture outcomes . Almost all included studies compared quality improvement strategies to control or usual care rather than an active comparator.…”
Section: Resultsmentioning
confidence: 99%
“…Meta‐analysis findings for strategies of multifaceted interventions targeting providers and patients, patient education and/or activation, and pharmacist initiation of screening in populations that included individuals without prior fracture did not show statistically significant improvement in outcomes of BMD/DXA testing or osteoporosis treatment. Furthermore, although we did not have enough similar studies that evaluated provider education and/or audit and feedback to perform meta‐analyses for these strategies, qualitative review of studies with interventions composed primarily of these strategies revealed that almost all of the studies did not find significant improvement in BMD testing and/or osteoporosis treatment outcomes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation